2022
DOI: 10.3389/fpsyg.2022.818454
|View full text |Cite
|
Sign up to set email alerts
|

The Idea Is Mine! An Empirical Examination on the Effect of Leaders’ Credit Claiming on Employees’ Work Outcomes

Abstract: Existing studies mainly explored the detrimental effect of employee credit claiming, and little is known about how leader credit claiming can affect employees. Based on affective events theory and relative deprivation theory, we explore how leader credit claiming affects employee work outcomes (i.e., voice behavior and job performance) by the research methods of literature review, interview, and empirical questionnaire. With a sample of 418 matched leader–employee pairs from a large manufacturing company, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Recently, research on supervisor humor in the organization has received increasing interest among scholars ( Gkorezis et al, 2011 ; Huo et al, 2012 ; Pundt and Herrmann, 2015 ; Kim et al, 2016 ; Cooper et al, 2018 ; Mesmer-Magnus et al, 2018 ; Liu et al, 2019 ; Tan et al, 2020 ; Rosenberg et al, 2021 ). Supervisor humor, a behavior enacted directed toward a subordinate by a supervisor that is intended to be amusing to the subordinate and that the subordinate perceives the act as intentional ( Cooper, 2005 ; Cooper et al, 2018 ), is particularly salient since supervisors hold power and have control over resources, and thus set the tone for humor use in the organization ( Cooper, 2005 ; Pundt and Herrmann, 2015 ; Li et al, 2021 ; Wu et al, 2021 ; Chen et al, 2022 ). Empirical research has indicated that supervisor humor is positively related to task performance ( Avolio et al, 1999 ), organizational citizenship behaviors ( Cooper et al, 2018 ), innovative behavior ( Pundt, 2015 ), work engagement ( Yam et al, 2018 ), job satisfaction ( Mesmer-Magnus et al, 2018 ), and leader-member exchange ( Pundt and Herrmann, 2015 ; Tremblay, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research on supervisor humor in the organization has received increasing interest among scholars ( Gkorezis et al, 2011 ; Huo et al, 2012 ; Pundt and Herrmann, 2015 ; Kim et al, 2016 ; Cooper et al, 2018 ; Mesmer-Magnus et al, 2018 ; Liu et al, 2019 ; Tan et al, 2020 ; Rosenberg et al, 2021 ). Supervisor humor, a behavior enacted directed toward a subordinate by a supervisor that is intended to be amusing to the subordinate and that the subordinate perceives the act as intentional ( Cooper, 2005 ; Cooper et al, 2018 ), is particularly salient since supervisors hold power and have control over resources, and thus set the tone for humor use in the organization ( Cooper, 2005 ; Pundt and Herrmann, 2015 ; Li et al, 2021 ; Wu et al, 2021 ; Chen et al, 2022 ). Empirical research has indicated that supervisor humor is positively related to task performance ( Avolio et al, 1999 ), organizational citizenship behaviors ( Cooper et al, 2018 ), innovative behavior ( Pundt, 2015 ), work engagement ( Yam et al, 2018 ), job satisfaction ( Mesmer-Magnus et al, 2018 ), and leader-member exchange ( Pundt and Herrmann, 2015 ; Tremblay, 2021 ).…”
Section: Introductionmentioning
confidence: 99%